STAVROPOL BOLSHEVIKS IN 1917: FROM ATTEMPTS OF COOPERATION TO SEIZING THE POWER - E. Y. Oborskiy (Гуманитарные и юридические исследования)
The article studies the activities of Stavropol Bolsheviks during the Russian Revolution of 1917. The focus is on their efforts to cooperate with the new state authorities. The article outlines the conditions for establishing Soviet power in the Stavropol region led by Bolsheviks.